Monitoreo del búho terrestre (Athene Cunicularia) en el aeropuerto internacional Cotopaxi de la ciudad de Latacunga” - Camino Mena, José Luis (2024)
The present research was carried out with the objective of understanding the ecology of the Burrowing Owl (Athene cunicularia) of the Strigiformes Order within the Strigidae family at the Cotopaxi International Airport located in the Cotopaxi province, Latacunga canton, with a comprehensive approach covering its census, diet, and the variation of the latter in relation to climatological variables during the months of September, October, and November. The census of the diurnal bird was carried out using the direct observation counting method, which involves on-site visits and a linear transect technique alongside the airplane runway within the airport, allowing for an estimation of nineteen Athene cunicularia individuals per km2 of population density. In the field, a total of ten burrows were determined, with approximately 3 individuals inhabiting each one. Regarding the diet, analysis of 243 pellets was conducted in the laboratory through dissection, identifying 1141 prey items, belonging to species such as (Rattus rattus, Mus musculus, Microryzomys latissimus), anurans (Pristimantis curtipes), bats (Chiroptera), and five invertebrates (Coleoptera, Dermaptera, Orthoptera, Araneae, Scorpiones). Insects were the most predominant in their diet. Additionally, the variation in the owls' diet in relation to climatological variables such as precipitation and prey availability was analyzed. Two analyses were conducted using the likelihood ratio test. The first analysis aimed to determine if there were differences among burrows in prey usage, while the second analysis aimed to ascertain if all burrows differed in the usage of certain prey items during the months of September, October, and November